Twenty years of legal marriage for same-sex couples in the United States evidence review and new analyses - Karney, Benjamin R. 1968- (RAND, 2024)
"Twenty years ago, the United States was divided by heated debates over legalizing marriage for same-sex couples. Those in favor argued that granting same-sex couples access to marriage would strengthen commitment for same-sex couples, extend the financial benefits of marriage to same-sex households, and improve outcomes for children raised by same-sex parents. Those who were opposed argued that granting legal status to marriages between same-sex partners would alter the foundation of marriage and diminish its value for different-sex couples, ultimately harming children by making them less likely to be raised in stable, two-parent families. It has now been 20 years since Massachusetts became the first state to issue marriage licenses to same-sex couples in May 2004. The consequences of extending legal recognition to same-sex couples need no longer be a topic of speculation and debate; researchers have had two decades to study the consequences of legalizing marriage for same-sex couples on lesbian, gay, bisexual, and transgender (LGBT) individuals; their children; and the general public. The broad goal of this report is to document those consequences. The authors pursued this goal in two ways. First, they conducted a comprehensive review of the existing research literature on the effects of legalizing marriage for same-sex couples. Second, they conducted new analyses to evaluate the prediction that rates of marriage, cohabitation, and divorce and attitudes toward marriage would be adversely affected by granting same-sex couples access to legal marriage."
Keywords: Geschichte 2004-2024; Gleichgeschlechtliche Ehe; USA; Same-sex marriage / United States; Same-sex marriage / Law and legislation / United States; Children of gay parents / United States; Sexual minorities' families / United States; Children and Families Legislation; Courts; Government Legislation; LGBTQ+ Populations; Marriage and Divorce; United States; FAMILY & RELATIONSHIPS / General; HISTORY / United States / General; LAW / Business & Financial; LAW / Courts